2020
DOI: 10.3390/met11010061
|View full text |Cite
|
Sign up to set email alerts
|

Recrystallization Behavior of a Pure Cu Connection Interface with Ultrasonic Welding

Abstract: Three-dimensional metal waveguide components are key components in the next generation of radio telescopes. Ultrasonic additive manufacturing technology combining ultrasonic welding and micro electrical discharge machining (micro-EDM) provides a new method for the overall manufacturing of waveguide elements, and the effective welding of Electrolytic Tough Pitch copper (Cu-ETP) sheets is the key process of this method. This study demonstrates that the orthogonal test optimization method is used to conduct ultra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 30 publications
3
11
0
1
Order By: Relevance
“…To elucidate the nature of this effect, the fracture Our study has shown that the strength of weld joints non-monotonically depends on the clamping force. This behavior is typical for USW and has been observed, for example, on similar Cu-Cu and dissimilar Al-Cu joints [30,31]. The increase in strength with increasing P is usually explained by an increase in the bonded area in the contact zone.…”
Section: Lap Shear Strength Of Weld Jointssupporting
confidence: 54%
See 1 more Smart Citation
“…To elucidate the nature of this effect, the fracture Our study has shown that the strength of weld joints non-monotonically depends on the clamping force. This behavior is typical for USW and has been observed, for example, on similar Cu-Cu and dissimilar Al-Cu joints [30,31]. The increase in strength with increasing P is usually explained by an increase in the bonded area in the contact zone.…”
Section: Lap Shear Strength Of Weld Jointssupporting
confidence: 54%
“…Such structural changes are typical of non-uniformly deformed metals. A fine-grained layer is formed as a result of dynamic recrystallization near the contact surface of the welded specimens, where the magnitude of deformation and temperature have the highest values [30,38]. With increasing distance from the contact surface, the strain rapidly decreases, and the processes of dynamic recovery prevail, which leads to the formation of a developed LAB network.…”
Section: Microstructure Evolution In Cg Samples During Uswmentioning
confidence: 99%
“…Selama proses FSW akan terbentuk heat affected zone (HAZ), thermomechanical affected zone (TMAZ), dan daerah adukan las (weld nugget) [4]. Temperatur yang terjadi pada proses FSW berada di bawah temperatur leleh logam induk sehingga temperatur rekristalisasi akan berbeda dengan pengelasan konvensional [5]- [7]. HAZ yang terbentuk pada FZW mirip dengan las konvensional karena karena zona ini tidak mengalami deformasi.…”
Section: Pendahuluanunclassified
“…At the joint interface, the bonding area originates from sliding contact between base metals. As more contact areas are produced, a higher fraction of the surface metal is involved in the development of bonding areas due to bonding mechanisms such as local plastic deformation [15], surface wear [16], phase transformation [17] and dynamic recrystallisation [18][19][20].…”
Section: Introductionmentioning
confidence: 99%